The effect of metformin on proliferation and glucose uptake in keloid fibroblast culture - Nur Dwita Larasati, Sunardi Radiono Yohanes Widodo Wirohadidjojo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2009)
Background: Metformin as an antihyperglycemic agent has a potential effect in increasing type I collagen synthesis and decreasing MMP, so that it has a potential to be an antiaging agent. One of aging failure processes is the development of keloids. Keloids are formed due to hyperproliferation of fibroblasts, an increase of collagen synthesis, particularly type I and III, and a decrease in MMP-1 and MMP-2. Fibroblast proliferation process and collagen synthesis need glucose uptake. The study on metformin ability to aggravate or stimulate the formation of keloid has never been conducted before. Objective: The aim of this study was to know the difference of proliferation and glucose uptake between keloid fibroblasts given metformin and without metformin. Method: A simple experiment was conducted using 3rdpassage keloid fibroblasts culture. Keloid fibroblasts were divided into 2 groups, the first group was treated with metformin in the dose of 100 pg/mL, 200 pg/mL, 300 pg/ mL, 400 pg/mL, and control. Keloid fibroblasts proliferation in the first group was measured using spectrophotometer with MTT assay, and glucose uptake of keloid fibroblast in the other group was measured using glucometer. The difference in proliferation and glucose uptake of keloid fibroblast was analyzed using one-way anova. Result: The result of this study showed that the average keloid fibroblast proliferation in the metformin treatment groups was not increased compared to that in control group. Meanwhile, the average keloid fibroblast glucose consumption in metformin treatment group significantlyincreased, at the dose of 300 ig/mL (p =0.044) and 400 I!g/mL (p = 0.0081. Conclusion: Metformin could not increase keloid fibroblasts proliferation, but it could increase glucose uptake of keloid fibroblasts.